Criminal Policy About Kecubung Containing Addictive Substances According to Law Number 35 of 2009 Concerning Narcotics - Djoko Purwanto (Green Publisher Indonesia, 2021)
This paper raises problems related to the absence of regulation regarding kecubungwhich contains alkaloid substances known as anesthetics and is an addictive substance for Narcotics, substances which when consumed in excess can cause decreased and altered consciousness, loss of taste, eliminate or reduce pain and cause dependence. severe or excruciating pain. The absence of regulations regarding amethyst has resulted in a legal vacuum and this is very unfortunate. This journal research uses normative juridical research supported by empirical juridical, the research approach method used is the statute approach (statutory approach), the conceptual approach (conceptual approach) and the case approach (case approach) and the data analysis technique of this research uses interpretation techniques. systematic, grammatical interpretation and theological interpretation. The results of the study concluded that regulation of the use of Kecubung is very much needed, where later this regulation can be used as a basis for law enforcement officials, especially the Police and BNN to process the law against the new types of Narcotics abuse as referred to in Law Number 35 of 2009 concerning Narcotics and Permenkes Number 44 of 2019 concerning changes in the classification of Narcotics.